1994
DOI: 10.1002/jab.770050208
|View full text |Cite
|
Sign up to set email alerts
|

Six bioabsorbable polymers: In vitro acute toxicity of accumulated degradation products

Abstract: Bioabsorbable polymer implants may provide a viable alternative to metal implants for internal fracture fixation. One of the potential difficulties with absorbable implants is the possible toxicity of the polymeric degradation products especially if they accumulate and become concentrated. Accordingly, material evaluation must involve dose-response toxicity data as well as mechanical properties and degradation rates. In this study the toxicity and rates of degradation for six polymers were determined, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
242
2
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(267 citation statements)
references
References 9 publications
3
242
2
6
Order By: Relevance
“…It should be noted that the 14 d cultures were completed before the Vicryl fibers had completely dissolved. It has been shown that most of the toxic effect of PLA and PGA occurs after 10 d [41]. Therefore, whether or not the CPC-fiber composite is non-cytotoxic after 14 d remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the 14 d cultures were completed before the Vicryl fibers had completely dissolved. It has been shown that most of the toxic effect of PLA and PGA occurs after 10 d [41]. Therefore, whether or not the CPC-fiber composite is non-cytotoxic after 14 d remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…In general, PLA (and related polymers like PGA) have demonstrated good biocompatibility and absence of significant toxicity, although some reduction in cell proliferation has been reported on PLA in vitro [106,107]. Also, it has been reported that PLA produces toxic solutions in vitro, probably as a result of the acidic degradation products [94].…”
Section: Biocompatibility and Toxicitymentioning
confidence: 99%
“…Hollowel [46] reported that the endplate did not increase the resistance significantly when tested in compression until failure; Closkey [24] agreed but showed that a minimum contact area was needed to avoid subsidence. However, Steffen [94] and Polikeit [87,91] found that placement of cages in the central area of the vertebral body, whether the endplate has been removed or not, could cause early failure. More recently Lowe et al [70] showed that the central region of the endplate provided the least resistance.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Nevertheless, the most frequently investigated biodegradable materials such as poly(lactic acid) or poly(glycolic acid) produce acidic degradation products that may accumulate and become concentrated, leading to toxicity. 26 A biocompatibility polymer poly(trimethylene carbonate) (PTMC) with no influence on the pH was explored. The surface erosion of PTMC occurred only in the presence of lipase and thus provided constant release of the antibiotics.…”
Section: Biodegradable Materialsmentioning
confidence: 99%